(untitled) (Indian Journal of Child Health, 2014)
Introduction: Pneumococcal conjugate vaccines (PCV) have revolutionized the prevention of invasive pneumococcal disease (IPD) globally. The initial 7-valent (PCV7) vaccine has gradually been replaced by higher valency vaccines such as PCV10 and PCV13, as these cover additional serotypes causing increased immunization. Objective: The purpose of this study was to determine the overall attitude and practices of the Indian public toward PCV for their infants. Materials and Methods: Data were collected over a period of 18 months from a tertiary perinatal center. Pneumococcal vaccine leaflets with current, unbiased information on PCV10 and PCV13 were circulated to parents, who were then asked to opt for either one or none of the vaccines for their infants at their 6 weeks immunization check-up. Results: A total of 3406 infants came for follow-up. Among them, 84% chose to give the PCV while the remaining 16% opted out. Among the parents that opted for the vaccines, 90% chose PCV13 over PCV10. This may be attributable to its increased immunogenicity and broader serotype coverage as understood by the parents - who seem to want the best for their children. Conclusion: PCV13 was a preferred vaccine of choice for infants by majority of the parents, as compared to PCV10. Such information is of valuable importance in deciding which vaccine to go for if and when India goes for PCV in the future with Global Alliance for Vaccines and Immunization and United Nations Children’s Fund funding.